Impaired spatial processing in visual perception, imagery and art-making following parieto-occipital infarcts. (May 2020) - Foley, Jennifer A.; Bayraktar, Isik; Hyare, Harpreet; Caine, Diana
Abstract: Visual imagery, like vision as such, is widely thought to be supported by two distinct and dissociable processing streams, dedicated to object representation and spatial analysis respectively. However, this simple dichotomy has been contested, with recent studies suggesting that impairments in perception-for-action and visuo-spatial imagery may reflect a more general deficit in space-based attention. Although previous studies have revealed the impact of brain damage on artistic expression, few have examined the impact on artistic expression in terms of the perceptual and spatial components of either visual processing or visual imagery. Here we present the case of an artist whose artistic expression was dramatically affected following devastating posterior brain damage. Of particular interest, we demonstrate how these changes relate to impairments in integrating and aligning different spatial features in both visual processing and visual imagery, suggestive of a general simultanagnosia not previously described.